Added Sugars and Cardiovascular Disease Risk in Children: A Scientific Statement From the American Heart Association. Issue 19 (9th May 2017) - Vos, Miriam B.; Kaar, Jill L.; Welsh, Jean A.; Van Horn, Linda V.; Feig, Daniel I.; Anderson, Cheryl A.M.; Patel, Mahesh J.; Cruz Munos, Jessica; Krebs, Nancy F.; Xanthakos, Stavra A.; Johnson, Rachel K.
Abstract : Background: Poor lifestyle behaviors are leading causes of preventable diseases globally. Added sugars contribute to a diet that is energy dense but nutrient poor and increase risk of developing obesity, cardiovascular disease, hypertension, obesity-related cancers, and dental caries. Methods and Results: For this American Heart Association scientific statement, the writing group reviewed and graded the current scientific evidence for studies examining the cardiovascular health effects of added sugars on children. The available literature was subdivided into 5 broad subareas: effects on blood pressure, lipids, insulin resistance and diabetes mellitus, nonalcoholic fatty liver disease, and obesity. Conclusions: Associations between added sugars and increased cardiovascular disease risk factors among US children are present at levels far below current consumption levels. Strong evidence supports the association of added sugars with increased cardiovascular disease risk in children through increased energy intake, increased adiposity, and dyslipidemia. The committee found that it is reasonable to recommend that children consume ⩽25 g (100 cal or ≈6 teaspoons) of added sugars per day and to avoid added sugars for children <2 years of age. Although added sugars most likely can be safely consumed in low amounts as part of a healthy diet, few children achieve such levels, making this an important public health target.